Proportional Prevalence of Bovine Parasitic Diseases at Mymensingh District of Bangladesh - Haque, Resmina; Suraiya, Mst Jannatul; Islam, Md Aminul; Ehsan, Md Amimul; Rony, Sharmin Aqter (Research in Agriculture Livestock and Fisheries, 2025)
Parasitic diseases significantly hinder profitable cattle production in Bangladesh. This retrospective study aimed to determine the prevalence, risk factors, clinical signs, and treatment practices of common parasitic infections in cattle in the Mymensingh district. A total of 415 cases were analyzed from clinical records at the Veterinary Teaching Hospital, Bangladesh Agricultural University, between February 2022 and January 2023. The most common parasitic diseases were paramphistomiasis (49.81%), stomach worm infections (16.47%), fascioliasis (16.28%), ectoparasitoses (10.92%), balantidiasis (5.94%), and blood protozoal infections (0.57%). The highest number of cases was recorded from Mymensingh Sadar upazila (80.7%). Infections were more frequent in female cattle (51.80%) than in males (30.36%). Major clinical signs included diarrhea (39.80%), reduced milk production (22.33%), hair loss (17.47%), constipation (10.67%), abdominal distension (4.20%), fever (4.53%), and coffee-colored urine (0.97%). Mixed infections (73.97%) were more common than single infections (26.02%). Post-deworming recurrence was noted in cases of paramphistomiasis (28.95%), balantidiasis (26.31%), and fascioliasis (10.53%). The most prescribed treatment was a combination of triclabendazole and levamisole (52.30%), followed by fenbendazole (16.47%), ivermectin (10.92%), nitroxynil (9.19%), copper sulfate (5.94%), triclabendazole alone (4.56%), and imidocarb (0.57%). These findings highlight the high burden of parasitic infections and emphasize the need for routine deworming and improved management practices in modern cattle farming systems in Bangladesh. Res. Agric. Livest. Fish. Vol. 12, No. 2, August 2025: 231-241